Implementation of the Project-Based Learning Model to Improve Collaboration and Students' Growth Mindset - Himawan*, Nur Arviyanto; Istihapsari, Vita; Supriyanta, Supriyanta; Putri, Pretty Oktianti Menur Kusuma (Universitas Syiah Kuala, 2025)
Students' collaboration and mindset are essential aspects that must be developed in the physics learning process to foster strong self-regulation. This research aims to enhance the collaboration character and growth mindset of students by implementing the project-based learning (PjBL) model assisted by google sites. The research is a classroom action research conducted over two cycles in class X3 at Muhammadiyah SHS of Bantul. Data collection techniques involve non-test methods using an observation sheet. Data regarding collaboration and growth mindset characteristics were analyzed by calculating percentages and comparing them with the assessment categories obtained through standard deviation calculations. The results indicate a significant improvement in collaboration character, increasing from 53% (poor) in cycle I to 88% (very good) in cycle II. Additionally, the growth mindset improved from 56% (enough) in cycle I to 82% (good) in cycle II. These findings demonstrate that the PjBL model, assisted by google sites, has a positive impact on students' collaboration character and growth mindset